Protective effect of betulin against aluminium-induced Alzheimer-like neurodegeneration - Agnieszka Zakrzeska; Paweł Kitlas; Alexej Shlyahtun; Ryszard Jabłoński; Mikołaj Tomulewicz; Natalia Szymańska (Polskie Towarzystwo Farmaceutyczne, 2023)
The purpose of this study was to show the preventive properties of the botulin (Bet) and its combination with cyclodextrin in a model of neurodegenerative disease like Alzheimer's disease (AD) in rats. Betulin was obtained from birch bark using standard methodology. The AD model was induced by administering aluminum chloride AlCl3 (200 mg/kg/day) to animals for 120 days. All animals were divided into 4 groups: the control group (sham operation), the second - the AD model (Alz) without prevention with betulin, the third - the Alz+Bet receiving betulin (100 mg/kg/day, i.g., during the last 50% of the experimental days), and the Alz+Bet Complex receiving betulin in complex with cyclodextrin (100 mg/kg/day, i.g., during the last 50% of the experimental days). We showed that betulin in complex with cyclodextrin improve the spatial memory and lowered levels of the TNF-α, APLP2 and β-amyloid in rats with AlCl3-induced AD. We conclude that betulin has neuroprotective properties which may form the basis for the development of a new pharmaceutical that is effective in both the prevention and treatment of Alzheimer's disease.